How small differences grow over time - the snowball effect of grit on practice in sport - Cocic, D.; Larkin, P.; Hendry, D. T.; Williams, A. M.; O`Connor, D.; Bilalic, M. (International Journal of Sport and Exercise Psychology, 2025)
Domain-specific practice is crucial for expertise. While much is known about practice, less is understood about what motivates individuals to start and continue with the intensive domain-specific practice needed for expert performance. We demonstrate in a large sample (N = 388) of Australian elite youth soccer players that they retrospectively report different amounts of practice at various stages of development and that acquisition is driven by the personality trait of grit. Players reported consistently engaging in domain-specific activities every year from age 8 until 13 years. The estimated logged hours experienced a marked acceleration at the age of 13 years, resulting in an enhanced and curvilinear pattern of practice accumulation. Grittier players, however, start accumulating more practice at the beginning of the talent development process and continue to consistently log more hours throughout the years than less gritty players. Consequently, initially small differences in practice engagement between those with high and low grit scores, snowball into sizable ones at the age of 15 years. The impact of grit on practice accumulation is, however, more subtle, as grit`s two components, consistency of interest and perseverance of effort, exert a different pattern of influence. The driving factor of the initial differences and their consistent snowball effect until age 13 years is a consistency of interest, whereas the perseverance of effort aspect impacts the practice acceleration period from age 13 to age 15 years. We elaborate on these findings to explain the complex relationship between grit and practice on the path to performance excellence.